MiR‐145 attenuates cardiac fibrosis through the AKT/GSK‐3β/β‐catenin signaling pathway by directly targeting SOX9 in fibroblasts. Issue 2 (5th September 2020) - Cui, Shengyu; Liu, Zhebo; Tao, Bo; Fan, Suzhen; Pu, Yong; Meng, Xiangping; Li, Dongqing; Xia, Hao; Xu, Lin
Abstract: Myocardial infarction (MI) will inevitably result in cardiac fibrosis. In this study, we investigated the effect of microRNA‐145 (miR‐145) and transcription factor sex‐determining region Y box 9 (SOX9) in the production of cardiac fibrosis induced by MI. MI rat models were established by left anterior descending coronary artery (LAD) occlusion. Four weeks after LAD, the cardiac fibrosis level was assessed by Masson's trichrome staining. Cardiac fibroblasts (CFs) exposed to hypoxia were used to simulate MI‐induced fibrosis. Flow cytometry, cell counting kit‐8, and transwell assays were used to examine changes in CF apoptosis, proliferation, and migration, respectively. miR‐145 expression was measured by quantitative real‐time polymerase chain reaction. Immunofluorescence and Western blot analysis were performed to determine the relative expression of proteins. In comparison to the sham‐operated group, the expression of miR‐145 was significantly downregulated in the infarction peripheral area, whereas, SOX9 was upregulated. In the infarcted heart, the overexpression of miR‐145 significantly ameliorated cardiac fibrosis and cardiac function, and there was a negative correlation between miR‐145 and SOX9 expressions in hypoxic CFs in vitro. In addition, SOX9 was verified to be a functional target of miR‐145. Overexpression of miR‐145 or inhibition of SOX9 decreased CF proliferation, migration, and fibrosis, but augmented their apoptotic rate. Moreover, the upregulation of miR‐145 or suppression of SOX9 inhibited AKT and β‐catenin signaling in hypoxic CFs. Taken together, this study highlights a potential treatment for cardiac fibrosis through the targeted regulation of SOX9 by miR‐145, and our findings indicate that miR‐145 exerts anti‐fibrotic effects in MI via the negative regulation of SOX9 and its downstream AKT/GSK‐3β/β‐catenin pathways. Abstract : With sex‐determining region Y box 9 (SOX9) confirmed as a fibrosis‐promotion molecule in the heart, a new strategy for the elevation of miR‐145 to regulate SOX9 needs to be developed.